Three day oral course of Augmentin to treat chancroid. Issue 3 (June 1986) - Ndinya-Achola, J O; Nsanze, H; Karasira, P; Fransen, L; D'Costa, L J; Piot, P; Ronald, A R
Abstract : Amoxycillin and clavulanic acid (Augmentin; Beecham Research Laboratories) was used to treat patients with bacteriologically proved chancroid in three different dose regimens. A single dose of Augmentin (amoxycillin 3 g, clavulanic acid 350 mg) was found to be ineffective. A similar dose repeated after 24 hours was equally ineffective, but a dose (amoxycillin 500 mg, clavulanic acid 250 mg) given every 8 hours for three days was found to be effective. The drug was well tolerated and no side effects were noted in any of the patients treated.